Virtual collaborative writing in the workplace : computer-mediated communication technologies and processes - Hewett, Beth L.; Robidoux, Charlotte, 1965- (Hershey, PA : Information Science Reference, 2010)
'This book investigates the use of computer-mediated communication technologies and collaborative processes to facilitate effective interdependent collaboration in writing projects, especially in virtual workplace settings'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Business writing; Business communication; Virtual work teams; Telematics